Ottoman-Sumatran relations, 1849-1904 - Tekin, Alaeddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The main aim of this research is to examine diplomatic relations between the Ottoman Caliphate and the Sultanates of Aceh, Riau, and Jambi on the island of Sumatra between 1849 and 1904. In this context, the impact of the Pan-Islamism policy developed by the Ottoman Empire in Sumatra is an important development in these relations, involving examination of the factors of Hadramis, Ottoman Consuls, the Pan-Islamist press, Indonesian hajis, and khutbahs etc. The relationship between the Ottoman Empire and the Sumatran Sultanates in the second half of the nineteenth century has not been paid sufficient attention in the existing literature. This study addresses this academic gap by providing a holistic and comprehensive understanding of the relations between these states and peoples based on official archival documents. After analysing this relationship, the study answers why historical relations between Istanbul and Sumatra were ruptured in the sixteenth century and why they were largely dormant until 1849. The historical-analytical method is employed in the thesis. In the diplomatic relations that occurred in the period between 1849-1904, the original letters exchanged by the rulers are examined, and the dynamics in the establishment of these relations are determined with the help of these documents. It is very important to consider the methods used by the Ottomans in these relations, because of the role of the Ottoman Sultans as universal Islamic caliphs, and how this legacy was reinvigorated in the context of anti-colonial resistance against Western empires, particularly the Netherlands in the context of Sumatra. In brief, the study focuses on the diplomatic relations developed between the Ottoman Empire and the Sultanates of Aceh, Riau, and Jambi, and examines how these diplomatic relations evolved later on, and took the form of a Pan-Islamist relationship during the critical period of 1849-1904. The result of this study, the Ottoman Empire established a diplomatic relationship with these Sultanates on the island in the second half of the nineteenth century and it was concluded that the Caliphate had an impact on Sumatran people since the 1880s. This research emphasizes the need for an alternative historical approach for studying this relationship, as well as Pan-Islamism developments occurring in the Malay World.